v(4v-24)=-6

Simple and best practice solution for v(4v-24)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for v(4v-24)=-6 equation:


Simplifying
v(4v + -24) = -6

Reorder the terms:
v(-24 + 4v) = -6
(-24 * v + 4v * v) = -6
(-24v + 4v2) = -6

Solving
-24v + 4v2 = -6

Solving for variable 'v'.

Reorder the terms:
6 + -24v + 4v2 = -6 + 6

Combine like terms: -6 + 6 = 0
6 + -24v + 4v2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(3 + -12v + 2v2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(3 + -12v + 2v2)' equal to zero and attempt to solve: Simplifying 3 + -12v + 2v2 = 0 Solving 3 + -12v + 2v2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. 1.5 + -6v + v2 = 0 Move the constant term to the right: Add '-1.5' to each side of the equation. 1.5 + -6v + -1.5 + v2 = 0 + -1.5 Reorder the terms: 1.5 + -1.5 + -6v + v2 = 0 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + -6v + v2 = 0 + -1.5 -6v + v2 = 0 + -1.5 Combine like terms: 0 + -1.5 = -1.5 -6v + v2 = -1.5 The v term is -6v. Take half its coefficient (-3). Square it (9) and add it to both sides. Add '9' to each side of the equation. -6v + 9 + v2 = -1.5 + 9 Reorder the terms: 9 + -6v + v2 = -1.5 + 9 Combine like terms: -1.5 + 9 = 7.5 9 + -6v + v2 = 7.5 Factor a perfect square on the left side: (v + -3)(v + -3) = 7.5 Calculate the square root of the right side: 2.738612788 Break this problem into two subproblems by setting (v + -3) equal to 2.738612788 and -2.738612788.

Subproblem 1

v + -3 = 2.738612788 Simplifying v + -3 = 2.738612788 Reorder the terms: -3 + v = 2.738612788 Solving -3 + v = 2.738612788 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + v = 2.738612788 + 3 Combine like terms: -3 + 3 = 0 0 + v = 2.738612788 + 3 v = 2.738612788 + 3 Combine like terms: 2.738612788 + 3 = 5.738612788 v = 5.738612788 Simplifying v = 5.738612788

Subproblem 2

v + -3 = -2.738612788 Simplifying v + -3 = -2.738612788 Reorder the terms: -3 + v = -2.738612788 Solving -3 + v = -2.738612788 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + v = -2.738612788 + 3 Combine like terms: -3 + 3 = 0 0 + v = -2.738612788 + 3 v = -2.738612788 + 3 Combine like terms: -2.738612788 + 3 = 0.261387212 v = 0.261387212 Simplifying v = 0.261387212

Solution

The solution to the problem is based on the solutions from the subproblems. v = {5.738612788, 0.261387212}

Solution

v = {5.738612788, 0.261387212}

See similar equations:

| -8y+5=-9y+3 | | h^2+26h-10=0 | | -6y+4=7y+5 | | 27x+13x=73 | | 3x^2-3x+5=0 | | 5p+5=7-4p | | x-2x+5=5 | | X^2+11x+13=0 | | (3x+7)(x+1)=10 | | 9-41= | | x^2-30x+125=0 | | 2x(x+8)+15=0 | | g^2-8g+11=0 | | 2x-5y=1 | | 5(x+6)=8+5x | | 3x^2+2x+8=0 | | d^2+22d+121=18 | | 8x+3y=8 | | 9x^10=4x^9+41 | | b^2-8b+17=7 | | 15x^2=3x+7 | | 4p+3=10+3p | | 4p+3=10+3 | | 7x+2y=2 | | 4x+16-18=-8x+2 | | 6.8x-1=5.8x | | 60x^2*y^4=x | | 5x+y=13 | | m^2+14=8m | | -5p^2=30p+40 | | 7(x+9)=4[x-(8-x)] | | 4(3+5x)-4=3+2(x-2) |

Equations solver categories